Some thoughts on language of instruction at the University of the Philippines Diliman - Gaerlan, Barbara (EDUKASYON, 1995)
"Gaerlan discusses some issues regarding the language of instruction at UP Diliman. She states that despite the passage of a language policy in 1989 under President Abueva, which declared Filipino as the medium of instruction for undergraduate classes within a reasonable time frame, English still continues to dominate majority of the classes at UP.